PENGEMBANGAN LKPD PROBLEM-BASED LEARNING BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN SELF-EFFICACY - Zawahir Nafisah; Ramadhani Ramadhani (Universitas Muhammadiyah Semarang, 2025)
This research develops Culturally Responsive Teaching (CRT)-based Problem-Based Learning (PBL) worksheets for teaching triangles and quadrilaterals in junior high school mathematics, addressing the current lack of culturally relevant intructional materials. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved 31 eighth-grade students at UPT SMP Negeri 8 Medan to create and test worksheets that integrate local cultural contexts with mathematical problem-solving. Expert validation yielded excellent results (96% for design and 95% for content), while both students (82,12%) and teachers (95%) rated the materials as highly practical. Effectiveness testing showed moderate but significant improvement, with N-Gain scores of 0,68 for problem-solving skills and 0,56 for self-efficacy, indicating that these culturally-responsive PBL worksheets are valid, practical, and moderately effective for enhancing mathematical competencies. The findings demonstrate that embedding cultural relevance in mathematics education through carefully designed PBL worksheets can effectively support both cognitive and affective learning outcomes in geometry instruction.